ANALISIS PENGARUH STRATEGI MARKETING MIX TERHADAP KEPUASAN PELANGGAN DI TOKO SUGENG - Farida Nur Solikhah; Bambang Mursito; Supawi Pawenang (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to analyze the effect of the marketing mix strategy on customer decisions at Toko Sugeng. This research uses the mix method. The strategy used is squential explanatory. The research were obtained from questionnaires, interviews, observation and documentation. The population in this study are all customers who have made repeat purchases. Samples taken as many as 100 customers. Result research shows the effect of price on customer satisfaction is 14,726%. The effect of the product on customer satisfaction is 13.764%. Effect of location on customer satisfaction of 18,470%. The effect of promotion on customer satisfaction is equal to 37.074%. The effect of price, product, location, and promotion on customer satisfaction is 84%. The marketing strategy applied by Toko Sugeng in increasing customer satisfaction, namely by implementing a marketing formulation strategy, segmenting, targeting, positioning and the marketing mix strategy or marketing mix which consists of four elements, namely product, price, place, promotion. The purpose of this is to attract buyers and retain existing customers. Toko Sugeng uses a SWOT analysis for improve customer satisfaction. In the calculation of the SWOT analysis both in terms of the matrix, EFAS and IFAS and the Cartesian diagram, show that Toko Sugeng is in the quadrant I position, namely (+, +). This position proves a strong and likely shop. Tactic recommendations given is progressive. So that it is really possible to continue to expand, enlarge growth and achieve maximum progress. Keywords: marketing mix, strategy, customer satisfaction